162k views
1 vote
6x + 1 - 5x = 2
What is x=


6x + 1 - 5x = 2 What is x= -example-1
User Dayzza
by
5.1k points

2 Answers

5 votes

Answer:

x=1

Explanation:

Let's solve your equation step-by-step.

6x+1−5x=2

Step 1: Simplify both sides of the equation.

6x+1−5x=2

6x+1+−5x=2

(6x+−5x)+(1)=2(Combine Like Terms)

x+1=2

x+1=2

Step 2: Subtract 1 from both sides.

x+1−1=2−1

x=1

Answer:

x=1

User Jens Wegar
by
5.5k points
7 votes

Answer:

X=1

Explanation:

You want to start by collecting like terms (6x and 5x) which creates:

x+1=2

Move the constant to the right hand side and change the sign:

x=2-1

Calculate

x=1

User Vashon
by
5.0k points